Intenção estratégica e identidade organizacional: um estudo sobre formação da estratégia em uma organização inovadora - Daniel Teodoro Gomes (2012)
Aiming to contribute to the understanding of strategy as a formation process, this research proposes the following question: How the strategy of an innovative company is formed and which informal factors manifest in this process?. Informal factors are related to semiconscious processes of decision making, and cultural, political and historical aspects of an organization and the way these are perceived and interpreted by its members. In order to identify the informal factors, this research focus on two main concepts: strategic intent (HAMEL; PRAHALAD, 1989) and organizational identity (ALBERT; WHETTEN, 1985), defined as the members' perceptions about the future perspective and the present characteristics of the organization, respectively. To answer the proposed question, this research uses a case study on an innovative company, leader in its sector and the first provider of many mobile services in Brazil. Semi-structured interviews with directors and middle managers who participated in the strategy formation process are the main data collection instrument, complemented by documents and direct observation. The analysis is based on discourse analysis techniques, mainly the persuasion strategies suggest by Faria and Linhares (1993). The strategy of the studied company can be defined as an entrepreneurial vision aimed to revenue growth and value increase of the company, supported by a process of diversification of its products lines by means of a new direction composed of three elements: componentization; market segmentation in verticals; and the search for external resources to finance the recovery of innovation processes. The componentization presents itself as the central element of this new direction and, together with the concept of 3 Rs (reduce, recycle and re-utilization), is perceived by the company's members as a way of thinking, which can be applied to all its processes. Considering the proposals of researchers who support their work on empirical studies and theories developed in many fields of social sciences, this conclusioncan be put in other words: the strategy of the studied company is formed by an heuristic, in the case, supported by a deliberated perspective about the future of the company conditioned by its historical trajectory and central values -, which acts as a motivational factor and a guide for the decisions and actions of the organization members.